The Quantum 3D Superparticle - Mezincescu, L.; Townsend, P.K. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
The minimal (N=1) superparticle in three spacetime dimensions (3D) is quantized. For non-zero mass it describes a spin-1/4 semion supermultiplet of ''relativistic helicities'' (−1/4,1/4). The addition of a parity-violating Lorentz-Wess-Zumino term shifts this to (β−1/4,β+1/4) for arbitrary β. For zero mass, in which case spin is not defined, the quantum superparticle describes a supermultiplet of one boson and one fermion.